The methodology of delivering fatwas and ruling answers: a contemporary perspective in Malaysia / Muhammad Asyraf Mohd Ridzuan, Muhd Imran Abd Razak, Paiz Hassan, Muhammad Yusri Yusof @Salleh and Nurhidha Irawaty Kasmaruddin - Mohd Ridzuan, Muhammad Asyraf; Abd Razak, Muhd Imran; Hassan, Paiz; Yusof @Salleh, Muhammad Yusri (UiTM Cawangan Johor, 2024)
The way fatwas are delivered in modern Malaysia is crucial for guiding Muslims effectively in today's world. Without appropriate and effective delivery methods, fatwas and legal rulings are feared to be unable to achieve objectives and may even tarnish the image of Islam and religious scholars. This paper which is based on qualitative research, looks at different aspects of this process. It starts by explaining ho111 fatwas are viewed in Islam and then looks at how they are practiced in Malaysia, distinguishing between official and unofficial fatwas. The paper stresses the importance of considering society and the law when issuing fatwas. In understanding the reality of the questioner and society, the paper emphasies the need to adapt fatwas to local customs and culture. It suggests moving away from blindly following old interpretations and instead encourages scholars to address modern challenges through thoughtful interpretation. The paper also emphasies the importance of making fatwas easy to understand and not burdensome, in line with Islam's focus on practicality. It suggests that fatwas should be presented clearly and logically, supported by strong arguments and evidence, to gain credibility and acceptance. Lastly, the paper discusses using modern thenology like online platforms and mobile apps to reach more people with fatwas. It mentions the role of social media and multimedia in helping people engage with religious rulings. In conclusion, the paper highlights the need for a systematic and relevant approach to issuing fatwas in Malaysia. By focusing on clarity, relevance, and accessibility, Islamic scholars can ensure that fatwas continue to guide Muslims in navigating modern life while staying true to Shariah ruling.